Autonomous Authentication and Light Weight Key Management Scheme for Communication in Smart Metering Infrastructure - Dr.KP. Noufal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A smart grid (SG) comprises several subsystems and networks which works collectively; many subsystems are vulnerable and thus are possible for attacks from remote areas. Smart Grids have evolved as the power system for the next generation which transform the standard functions of the electrical grids. In smart grids, Advanced Metering Infrastructure (AMI) is considered as one key element containing systems and networks whose major function is to collect and analyze the data obtained from smart meters. Moreover, AMI manages various power related applications and services provided are based on the data gathered from smart meters. Hence the major role of AMI is to provide smooth functions by smart grids. Malicious challengers have massive chances to attack AMI and moreover system are extremely vulnerable to these attacks. Thus, AMI has to be necessarily secured as attackers may potentially damage the infrastructure by chance and cause privacy threats in SG. Among several challenges, the two most aspects considered are producing low-latency and offering real-time services in traditional smart grid systems. Moreover, the most identified challenge is the Key Management Scheme (KMS) which plays a major role in sustaining the AMI security. To overcome these problems, block chain based authentication and four novel key management schemes are proposed in this paper for AMI aiming to produce low latency and secure data in SG. In these schemes, individual and batch rekeying function are performed with the help of a innovative multi-group key graph structure, supporting unicast, broadcast and multicast communications. From analysis, it is observed that the proposed authentication and key management schemes are efficient in preventing different kind of attacks and also reduces the management overhead. Performance analysis and security assurance are discussed which demonstrates these desirable characteristics of the proposed method.